Production and Characterization of Coffee Husk Fuel Briquettes as an Alternative Energy Source - Assefa Tesfaye; Fentahun Workie; Venkatesh S. Kumar (Advances in Materials Science and Engineering)
Biomass energy accounts for more than 92 percent of overall energy consumption in Ethiopia. As a result, Ethiopia is one of the world’s most biomass-dependent countries. The high reliance on wood fuels and agricultural residues for fuel harms society’s social, economic, and environmental well-being. This study aims to create and test the quality of fuel briquettes made from the coffee husk. Also built and produced are a carboniser/charcoal kiln, a manually operated molder system, and a briquette stove for burning the manufactured briquette. The carboniser converts 15 kg of raw coffee husk into 6 kg of carbonised char in 25 minutes, and the manually operated briquette molder can press 30 kg per hour. The efficiency of converting raw coffee husk into carbonised char content was 40.12%. In the geological survey of Ethiopia, the geochemical laboratory directorate received triplicate samples of the fuel briquette charcoal for analysis. Moisture content, fixed carbon content, ash content, sulfur content, and calorific value were determined using a bomb calorimeter and a ceramic lining furnace. Physical properties of fuel briquettes ranged from 10.03% moisture content, 970 kg/m3 density, 81% fixed carbon, 5.15% ash content, 0% sulfur, and 30.54 Kcal/kg higher heating value, according to laboratory results. The results of the study revealed that the coffee husk fuel briquettes produced have more positive characteristics. Fuel briquettes were cost-effective and environmentally friendly and reduced deforestation compared to firewood. This study clearly shows that briquettes made from coffee husk could be used as an alternative energy source when this kind of waste is well managed.